2014
DOI: 10.1371/journal.ppat.1004225
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Empirical Antibiotic Therapy in Hospitals: Meta-Analysis and Models

Abstract: The rise of resistance together with the shortage of new broad-spectrum antibiotics underlines the urgency of optimizing the use of available drugs to minimize disease burden. Theoretical studies suggest that coordinating empirical usage of antibiotics in a hospital ward can contain the spread of resistance. However, theoretical and clinical studies came to different conclusions regarding the usefulness of rotating first-line therapy (cycling). Here, we performed a quantitative pathogen-specific meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 78 publications
1
103
1
Order By: Relevance
“…For example, starting patients on a single drug before adding a second drug promotes the evolution of multidrug resistance (8)(9)(10)(11). A similar effect is seen for studies that rotate antibiotics (12)(13)(14). Even if drugs are given simultaneously but have different in vivo half-lives (15)(16)(17) or postantibiotic effects (18), periods of "effective monotherapy" with the longer-lived drug can occur, which may favor resistance evolution.…”
mentioning
confidence: 86%
“…For example, starting patients on a single drug before adding a second drug promotes the evolution of multidrug resistance (8)(9)(10)(11). A similar effect is seen for studies that rotate antibiotics (12)(13)(14). Even if drugs are given simultaneously but have different in vivo half-lives (15)(16)(17) or postantibiotic effects (18), periods of "effective monotherapy" with the longer-lived drug can occur, which may favor resistance evolution.…”
mentioning
confidence: 86%
“…65 A meta-analysis showed that increased heterogeneity of prescribing was beneficial in reducing the incidence of all hospital-acquired infections and resistant infections. 66 Positive effects were also observed for most pathogens, and effects were particularly pronounced when baseline levels of resistance were low. 66 Therefore, selective use of cephalosporins, as part of a stewardship programme that delivers antibiotic diversity, could be an effective and well-tolerated therapeutic option.…”
Section: Antibiotic Strategies To Reduce CDI Riskmentioning
confidence: 98%
“…66 Positive effects were also observed for most pathogens, and effects were particularly pronounced when baseline levels of resistance were low. 66 Therefore, selective use of cephalosporins, as part of a stewardship programme that delivers antibiotic diversity, could be an effective and well-tolerated therapeutic option.…”
Section: Antibiotic Strategies To Reduce CDI Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…However, theoretical studies of one such approach, known as antimicrobial cycling, have shown that cycling reduces such contacts only under restricted conditions (34); in practice, cycling strategies are difficult to implement and to study (35). Recently, an alternative strategy, "adjustable cycling," in which treatment is changed when not effective in patients, has been proposed and shown in a theoretical model to suppress the emergence of MDR in most settings (36). The clinical impact of these linked determinants depends on their persistence as a linked group.…”
Section: Explanations For the Origin Of Mdr Strainsmentioning
confidence: 99%